Association between methylenetetrahydrofolate reductase C677T polymorphism and psoriasis: A meta‐analysis. Issue 2 (27th July 2015) - Wu, Dongze; Shi, Deshun; Yang, Li; Zhu, Xiaoliang
Abstract: Several studies have evaluated the associations between methylenetetrahydrofolate reductase (MTHFR) C677T and psoriasis. However, the results remain inconclusive. The objective of the present study was to conduct a qualitative and quantitative meta‐analysis investigating the associations between MTHFR C677T and psoriasis. A published work search of PubMed, Embase, Web of Science and Chinese National Knowledge Infrastructure database were conducted to identify all publications concerning MTHFR C677T polymorphism and psoriasis on 1 October 2014. The principal outcome measure for evaluating the strength of the association was crude odds ratios along with their corresponding 95% confidence intervals. Data were extracted and statistical analyses were implemented using STATA version 12.0 software. A total of 1179 psoriatic cases and 937 controls from five case–control studies concentrating on the association between MTHFR C677T polymorphism and psoriasis were included in this qualitative meta‐analysis. Pooled analysis revealed that there is no association between this polymorphism and susceptibility to psoriasis in dominant, recessive, allele and additive models under a random‐effect model. However, a marginal significant association was found in the overdominant model under fixed‐effect model. Subgroup analysis of ethnicity demonstrated that there is no association between MTHFR C677T polymorphism and either Asian or European psoriatic patients. In conclusion, MTHFR C677T polymorphism, qualitatively, is not a genetic factor for the pathogenesis of psoriasis but could quantitatively reflect the severity of psoriasis to some extent.